Validasi Website E-TLE Menggunakan Metode Design Thinking - Ld. Muh. Ahmad Ilham; Subardin Subardin; La Ode Saidi; Wa Ode Zukaida (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2023)
The purpose of this study is to find out the results of the validation of the E-TLE website design and have benefits as a reference in implementing E-TLE in Kendari City and its benefits for users in accessing E-TLE traffic information and knowing in real time if they commit traffic violations. This research was conducted in 5 stages, starting at the empathy stage by users by conducting surveys and interviews. After that, at the define stage, namely collecting information and related things by users and research subjects, tthen the ideate stage finds ideas from previous problems and information then at the prototype stage, namely making a design from the ideas obtained then the last testing stage at this stage using the System Usabillity Scale (SUS) method for the validation stage. The author's final result test used the System Usability Scale (SUS) test, which obtained adjective good and acceptable results, with a value of 79.4 and entered the grade A category with a percentile range of 85-89.